Needs of Caregivers of Patients with Head Trauma after Discharge And Level of its Fulfillment - Seyed Hassan Mohagheghi Niadekan; MohammadReza Yegane Rastekenari; Ezat Paryad; Zahra Atrkar-e Roshan (Guilan University of Medical Sciences, 2016)
Introduction: Traumatic Brain Injury (TBI) is one of the most important matters of public health in which people affected often lose their functional abilities and have dependent life and in result these patients a caregiver for care and support. Thus families are at front line of challenges and great stresses. Objective:The aim of this study was to determine needs of caregivers of patients with head trauma after discharge and level of its fulfillment in patients referring to one of educational- therapeutic center in Rasht city Methods:This is a cross-sectional descriptive-analytical study conducted on 51 family members of patients with head injury who were selected by census method from available samples in 2013. In this study two questionnaires of demographics and Standard Family Need Questionnaire (FNQ) were used for data collection and analyzed by descriptive statistics and Chi square, independent T Test, ANOVA and Exact Fischer tests Results: The most important need was related to subscale of health information and the least related to getting involved with caring. There was a significant relationship between level of caregivers needs and their occupational status (P<0.046), patients age range (P<0.023) and patients clinical condition (P<042). The maximum rate (3.49 ± 0.56) of need fulfillment was related to subscales of community support and health information and the minimum (2.965 ± 0.78) was related to instrumental support. There was a significant relationship between meeting the needs in all domains and health insurance (P<0.044). Conclusion: The most important family need was related to subscales of health information that were often met. Apprehension of needs and difficulties of caregivers lead to increase of awareness of nurses and other custodians of healthcare about the necessity of helping caregivers of patients with Traumatic Brain Injury